Carburized zinc alloy negative plate, preparation method thereof and zinc ion battery
The carburized zinc alloy negative electrode sheet prepared by powder metallurgy solves the problems of loose structure, discontinuous conduction paths, and easy corrosion prepared by zinc powder coating, and achieves the high energy density and long cycle stability of zinc ion batteries.
Patent Information
- Application Number
- CN202411746173.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-18
AI Technical Summary
In existing zinc ion batteries, the zinc electrode prepared by zinc powder coating method has problems such as loose structure, discontinuous conduction paths, easy corrosion, uneven surfaces, leading to zinc dendrites growth, short circuits of the battery and shortened service life.
Powder metallurgy method is used to mix zinc powder, first-class corrosion-resistant metal powder and conductive carbon material to prepare a carburized zinc alloy negative electrode sheet with uniform structure and stable structure. This method forms a negative electrode sheet with high zinc utilization, strong conductivity and corrosion resistance through steps such as sintering and rolling.
It significantly improves the long cycle stability and energy density of zinc ion batteries, extends the number of cycles and service life of the battery, and reduces production costs, and is suitable for large-scale industrial production.
Abstract
Description
Technical Field
[0001] The embodiments of the present application belong to the technical field of zinc ion batteries, and in particular, relate to a carburized zinc alloy negative electrode sheet, a preparation method thereof, and a zinc ion battery. Background Art
[0002] Aqueous zinc-ion batteries stand out in large-scale electrochemical energy storage systems due to their inherent advantages such as high theoretical capacity, high safety and low cost. At present, the industry often uses a coating method to prepare zinc electrodes by coating zinc powder on the current collector. However, the structure between the zinc powder particles with a spherical microstructure is relatively loose and lacks a continuous conductive path, which slows the diffusion of zinc ions and makes it difficult to fully utilize the zinc material, thereby reducing the actual energy density of the battery; the electrode made by coating the current collector with zinc powder is easily corroded when in contact with the electrolyte for a long time, thereby shortening the battery life, and its surface is uneven, which easily leads to the tip effect and the growth of zinc dendrites, causing battery short circuit and failure; in addition, the adhesive used in the preparation of zinc electrodes by the coating method will inevitably reduce the conductivity and increase the cost; therefore, it is necessary to provide a zinc negative electrode with a stable structure, high zinc utilization, corrosion resistance and strong conductivity to effectively improve the long-cycle stability and energy density of aqueous zinc-ion batteries. Summary of the invention
[0003] In view of this, the present application provides a method for preparing a carburized zinc alloy negative electrode sheet, wherein zinc powder, a primary corrosion-resistant metal powder and a conductive carbon material are prepared into a carburized zinc alloy negative electrode sheet with uniform organization and stable structure by powder metallurgy, which has the advantages of high zinc utilization rate, strong conductivity and corrosion resistance. The carburized zinc alloy negative electrode sheet can significantly improve the long-cycle stability and energy density of zinc ion batteries, thereby extending the number of cycles and service life of the battery.
[0004] In a first aspect, the present application provides a method for preparing a carburized zinc alloy negative electrode sheet, comprising mixing zinc powder, a primary corrosion-resistant metal powder and a conductive carbon material to form a mixture, and using the mixture by powder metallurgy to prepare a carburized zinc alloy negative electrode sheet; wherein the mass percentage of the conductive carbon material in the mixture is 2%-5%.
[0005] Specifically, the conductive carbon material includes one or more of acetylene black, carbon fiber, graphene, carbon nanotube, conductive carbon black, conductive graphite, and Ketjen black.
[0006] Specifically, the specific surface area of the conductive carbon material is 60 m 2 / g-70m 2 / g.
[0007] Specifically, the primary corrosion-resistant metal powder includes one or more of chromium powder, nickel powder, molybdenum powder, titanium powder, zirconium powder, tantalum powder, tin powder, and niobium powder.
[0008] Specifically, the D50 particle size of the zinc powder and the primary corrosion-resistant metal powder is 0.1 μm-0.5 μm; and / or the mass percentage of the primary corrosion-resistant metal powder in the mixture is 2%-4%.
[0009] Specifically, the process of preparing the carburized zinc alloy negative electrode sheet by powder metallurgy is as follows: the mixed material is subjected to sheet pressing, sintering, cooling, slicing and rolling in sequence to obtain the carburized zinc alloy negative electrode sheet.
[0010] Specifically, the sintering is carried out under a negative pressure of 10 MPa-15 MPa, the sintering temperature is 450° C.-750° C., and the sintering time is 2 h-4 h.
[0011] Specifically, the conductivity of the carburized zinc alloy negative electrode sheet is 0.8×10 4 S / m-1.2×10 4 S / m; and / or, the compaction density of the carburized zinc alloy negative electrode sheet is 6.1g / cm 3 -7g / cm 3 .
[0012] In a second aspect, the present application provides a carburized zinc alloy negative electrode sheet, which is prepared by the preparation method provided in the first aspect of the present application.
[0013] In a third aspect, the present application further provides a zinc ion battery, which includes a carburized zinc alloy negative electrode sheet prepared by the preparation method provided in the first aspect of the present application. DETAILED DESCRIPTION
[0014] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0015] Unless otherwise specified, the raw materials used in the embodiments of the present invention are all commercially available products.
[0016] Tip effect: The sharper the object, the greater the force, and the stronger the physical effect (force, heat, light, electricity, magnetism). In batteries, zinc ion deposition occurs preferentially at protrusions, and the zinc dendrites formed may pierce the battery separator, causing the battery to short-circuit and fail, or break from the root, lose electrical contact and turn into "dead zinc" that does not contribute to capacitance.
[0017] Corrosion side reaction: During the discharge process, the zinc negative electrode undergoes a reaction where metallic zinc is converted into zinc ions, and the surface is filled with positive charges, which attracts SO4 in the electrolyte. 2+ and OH -A complex reaction occurs, and the solubility of the complex product formed is very limited. When it is supersaturated in the electrolyte, it will be deposited on the surface of the zinc negative electrode. The formation of these by-products is at the expense of continuous consumption of electrolyte and active zinc ions, which will reduce zinc deposition to a certain extent, thereby adversely affecting the reversibility of the zinc negative electrode.
[0018] Battery energy density: the amount of electrical energy stored or released by a battery per unit mass or unit volume.
[0019] Battery cycle performance: three indicators in the process of continuous and repeated charge and discharge, ① the number of battery cycles, ② the first discharge capacity after full charge, and ③ the retained capacity after multiple cycles.
[0020] Aqueous ion battery: also known as salt water battery. The biggest difference from traditional batteries is that salt water electrolyte is used to replace the flammable and explosive organic phase electrolyte. It is highly safe and environmentally friendly.
[0021] Symmetrical battery: A battery in which the positive and negative electrodes use the same electrode material to achieve symmetry. It is often used to study the various properties of battery electrodes.
[0022] Level 1 corrosion-resistant metal: The "Corrosion Data and Material Selection Manual" stipulates a four-level assessment standard for metal corrosion resistance, among which level 1 corrosion-resistant metal refers to metal with a corrosion rate of less than 0.05mm / a, which means that within one year, its corrosion depth does not exceed 0.05mm.
[0023] D50 particle size: The particle size corresponding to when the cumulative particle size distribution percentage reaches 50%, also called median particle size or median particle size.
[0024] Specific surface area: the total area per unit mass of material.
[0025] Aqueous zinc-ion batteries have aqueous electrolytes, which avoid the safety hazards of flammability and explosion caused by organic electrolytes in traditional batteries. They also have high theoretical capacity and low cost, making them stand out in large-scale electrochemical energy storage systems. However, zinc negative electrodes have problems such as zinc dendrites, corrosion, and hydrogen evolution reaction during battery cycling. At present, technical personnel in the industry are mainly working on solving the problems of zinc negative electrodes from the aspects of zinc electrode structure design, zinc electrode surface protective layer design, and hydrogel electrolytes replacing electrolytes and diaphragms. Among them, due to the low cost and good processing performance of zinc powder, the industry often adopts the coating method to coat zinc powder on the current collector to prepare zinc electrodes. However, the zinc electrodes prepared by the zinc powder coating method also have the following problems: First, the spherical microstructure of zinc powder will lead to a loose structure between zinc powder particles and lack of continuous conductive paths, thereby having a high internal resistance, slowing down the kinetic diffusion rate of zinc ions, and ultimately reducing the utilization rate of zinc and the actual energy density of the battery; second, the microscopic surface of the zinc electrode prepared by the coating method is uneven, which is easy to cause the tip effect, that is, zinc is more likely to be deposited on the raised part of the electrode surface, and the zinc dendrites formed thereby will pierce the diaphragm, causing battery short circuit and failure; third, the binder used in the coating method will also reduce the conductivity to a certain extent and increase the cost; fourth, the zinc negative electrode prepared by the coating method requires a metal foil current collector as a substrate, and metal foil, especially copper foil, often undergoes corrosion side reactions, and the products of the corrosion side reactions will cause irreversible damage to the battery.
[0026] In view of this, the embodiments of the present application provide a carburized zinc alloy negative electrode sheet, a preparation method thereof, and a zinc ion battery, wherein a primary corrosion-resistant metal and a conductive carbon material are introduced into metallic zinc, and the carburized zinc alloy negative electrode sheet prepared by powder metallurgy is sintered as an integral unit, and has uniform organization, stable structure, and no problems such as powder loss or surface detachment. Meanwhile, it has the advantages of high zinc utilization rate, strong conductivity, and corrosion resistance, and can effectively improve the long-cycle stability and energy density of the battery. Moreover, the preparation method is simple, easy, low-cost, high in material utilization rate, and environmentally friendly, and is suitable for industrial production.
[0027] The present application provides a method for preparing a carburized zinc alloy negative electrode sheet, comprising the following steps:
[0028] S101, mixing zinc powder, primary corrosion-resistant metal powder and conductive carbon material to obtain a mixture, wherein the mass ratio of the conductive carbon material in the mixture is 2%-5%;
[0029] S102, using the mixture obtained in step S101 to prepare a carburized zinc alloy negative electrode sheet by powder metallurgy.
[0030] The preparation method provided by the present application adopts powder metallurgy to make zinc powder, primary corrosion-resistant metal powder and conductive carbon material into carburized zinc alloy, and finally obtains a carburized zinc alloy negative electrode sheet with a preset size and shape that can be used as a battery electrode. Among them, zinc, as the main component of the carburized zinc alloy negative electrode sheet, switches zinc and zinc ions through redox reactions in the battery cycle, thereby realizing the mutual conversion of chemical energy and electrical energy; the introduction of a primary corrosion-resistant metal can enhance the corrosion resistance of the zinc negative electrode, thereby slowing down the corrosion rate of the zinc alloy negative electrode when it is in contact with the electrolyte for a long time, and at the same time can also improve its strength and hardness; the conductive carbon material can form a continuous three-dimensional conductive network when it is evenly distributed inside the alloy, providing a smooth mobile path for electron transmission, reducing internal resistance, thereby effectively improving the conductivity of the zinc negative electrode. The powder metallurgy method can ensure the uniformity and integration of each component, and the carburized zinc alloy negative electrode sheet obtained thereby has a compact organization, a stable structure, and a high zinc utilization rate, and the method is simple, low-cost, and pollution-free, and is suitable for large-scale industrial production.
[0031] In step S101, the conductive carbon material includes one or more of acetylene black, carbon fiber, graphene, carbon nanotubes, conductive carbon black, conductive graphite, and Ketjen black. The special structure of the carbon material makes it have good conductivity. For example, each carbon atom in the graphene is covalently bonded with three adjacent carbon atoms to form a hexagonal honeycomb. These covalent bonds allow electrons to move freely in the graphene sheet to form a conductive path; for example, carbon black particles are aggregated into a chain or branched structure. The more particles in the aggregate, the easier it is to form a conductive network; for example, carbon fiber is a high-strength, high-modulus fiber material that not only has conductivity, but also has the advantages of low density and good mechanical properties. In addition, the carbon material also has a high roughness and rich microscopic pore structure, which makes it difficult for water molecules to stay and condense on its surface, so it also has a certain hydrophobicity. In some specific embodiments of the present application, the conductive carbon material can be acetylene black or carbon fiber.
[0032] In the embodiment of the present application, the conductive carbon material may be in a powdery, fibrous, or flake form.
[0033] In the embodiments of the present application, the mass percentage of the conductive carbon material in the mixture is 2%-5%, for example, it can be but not limited to 2%, 2.5%, 3%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.5%, 4.8%, 5%. In some specific embodiments of the present application, the mass percentage of the conductive carbon material in the mixture is 3.5%-4.5%. Introducing a proper amount of carbon material into the zinc alloy can enhance its conductivity, while avoiding a large amount of carbon aggregation leading to uneven alloy components, forming an unsmooth conductive network and affecting electron transmission, and can also avoid excessive conductivity and excessive acceleration of electron transmission speed and electrochemical reaction speed during charging and discharging, thereby affecting the cycle life and safety of the battery.
[0034] In the embodiment of the present application, the specific surface area of the conductive carbon material is 60m 2 / g-70m 2 / g, for example, but not limited to 60m 2 / g, 61m 2 / g, 62m 2 / g, 63m 2 / g, 64m 2 / g, 65m 2 / g, 66m 2 / g, 67m 2 / g, 68m 2 / g, 69m 2 / g, 70m 2 / g. In some specific embodiments of the present application, the specific surface area of the conductive carbon material is 60m 2 / g-65m 2 / g. The conductive carbon material in the electrode has a suitable specific surface area, which can improve the battery capacity while ensuring the cycle life: on the one hand, it can control the electrode material and the electrolyte to have a suitable contact area, which helps to accommodate more ions, speed up the transmission speed of ions and electrons, and thus improve the battery's capacity and charge and discharge speed; on the other hand, it can avoid excessive promotion of the reaction between the electrode material and the electrolyte due to its large specific surface area, resulting in more degradation products that have an adverse effect on the battery cycle.
[0035] The carbon element itself can promote grain refinement. Introducing conductive carbon materials into zinc alloys can increase strength and hardness, improve processing performance, and extend service life. In addition, due to the unique atomic structure and aggregation mode of conductive carbon materials, introducing them into zinc alloys can significantly improve the various properties of zinc alloys as battery negative electrodes: First, conductive carbon materials such as carbon black, carbon fibers, etc., often aggregate into three-dimensional bond dendrites or form fibrous aggregates. When mixed with other alloy components to form a carburized zinc alloy, this three-dimensional dendritic fiber structure can be evenly and continuously distributed inside the carburized zinc alloy, which can provide a continuous three-dimensional conductive network for subsequent use as a battery electrode, reducing the internal resistance of the electrode. In addition, this three-dimensional structure can retain some of the zinc electrode discharge byproducts in the carburized zinc alloy instead of being deposited there. On the surface of the zinc electrode, it helps to inhibit the growth of zinc dendrites, avoid the powdering and deformation of the zinc electrode, and extend the service life of the battery; secondly, the hydrophobicity of the carbon material helps to inhibit water molecules from entering the interior of the zinc negative electrode, further preventing the occurrence of corrosion side reactions, while also accelerating the desolvation of zinc ions, which helps with the deposition of zinc and promotes the charge and discharge reaction process of the battery; thirdly, carbon materials have the characteristics of low density and light weight. Introducing an appropriate amount of carbon material into the zinc alloy can reduce the density and weight of the electrode sheet, while increasing the electrical energy stored or released by the battery per unit mass or unit volume, that is, improving the energy density of the battery.
[0036] In the implementation manner of the present application, the primary corrosion-resistant metal powder includes one or more of chromium powder, nickel powder, molybdenum powder, titanium powder, zirconium powder, tantalum powder, tin powder, and niobium powder. The mass percentage of the primary corrosion-resistant metal powder in the mixture is 2%-4%, for example, but not limited to 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%. In some specific implementation manners of the present application, the primary corrosion-resistant metal powder can be chromium powder or nickel powder, and its mass percentage in the mixture is 2%-2.5%. An appropriate amount of primary corrosion-resistant metal can enhance the corrosion resistance of carburized zinc alloy, while avoiding excessive addition to increase the density and weight of carburized zinc alloy, affecting the energy density of the battery.
[0037] In the implementation manner of the present application, the mass percentage of zinc powder in the mixture is 90%-96%, for example, but not limited to 90%, 91%, 92%, 93%, 94%, 95%, 96%. In some specific implementation manners of the present application, the mass percentage of zinc powder in the mixture is 92%-95%. Metallic zinc is the main material of the carburized zinc alloy negative electrode sheet, which is used to store or release energy in the battery cycle. The zinc content in the carburized zinc alloy negative electrode sheet directly determines its cycle performance and battery capacity when used as the battery negative electrode.
[0038] In the implementation manner of the present application, the purity of the zinc powder, the primary corrosion-resistant metal powder and the conductive carbon material is greater than or equal to 99.5%, for example, but not limited to 99.5%, 99.6%, 99.7%, 99.8%, 99.9%, 99.99%. In some specific implementation manners of the present application, the purity of the zinc powder, the primary corrosion-resistant metal powder and the conductive carbon material is 99.9%-100%. Ensuring the high purity of each component in the carburizing zinc alloy raw material can prevent impurities from interfering with the operation of the battery.
[0039] In some embodiments of the present application, the D50 particle size of the zinc powder and the primary corrosion-resistant metal powder is 0.1 μm-0.5 μm, for example, but not limited to 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm. In some specific embodiments of the present application, the D50 particle size of the zinc powder and the corrosion-resistant metal powder is 0.1 μm-0.2 μm. The present application adopts powder metallurgy to prepare carburized zinc alloy negative electrode sheets. The selection of powder particle size is crucial. The appropriate particle size distribution can avoid powder aggregation or affect the charging effect of the powder, which helps to optimize the density and mechanical properties of the carburized zinc alloy negative electrode sheets.
[0040] In the present application embodiment, the mixing instrument includes but is not limited to one of vacuum induction furnace, ball mill, and rotary agitator. In some embodiments of the present application, the mixing process is carried out in a vacuum induction furnace, and the rotating speed is 60r / min-80r / min, for example, 60r / min, 65r / min, 70r / min, 75r / min, 80r / min; The mixing time is 60min-90min, for example, 60min, 65min, 70min, 75min, 80min, 85min, 90min. Evenly mixing zinc powder, a first-level corrosion-resistant metal powder, and conductive carbon material can ensure the component uniformity of carburized zinc alloy, and it is helpful to form a uniform and continuous three-dimensional conductive network inside the carburized zinc alloy, thereby enhancing its conductive performance, and also can avoid irregular deformation of the carburized zinc alloy due to uneven components in the subsequent sintering process.
[0041] In step S102, the mixture obtained in step S101 is made into a carburized zinc alloy negative electrode sheet by powder metallurgy. The specific process includes: the mixture is pressed, sintered, and cooled to obtain a carburized zinc alloy, and then sliced and rolled to obtain a carburized zinc alloy negative electrode sheet.
[0042] In the embodiment of the present application, the mixed material is pressed into sheets to obtain carburized zinc alloy compacts. This process can avoid powder stratification, facilitate the molding of the carburized zinc alloy, and also help control the density, strength and regular shape of the subsequent carburized zinc alloy negative electrode sheet to avoid it being too loose or too compact and affecting its internal resistance, sheet specific capacity, ion conversion efficiency and other performance as a battery electrode.
[0043] In the implementation manner of the present application, the sintering method includes one of negative pressure sintering, vacuum sintering, hot pressing sintering, and high temperature isostatic pressing sintering; the sintering furnace may be, for example, but not limited to, a vacuum sintering furnace, a tubular furnace, a box furnace, a kiln, a central melting furnace, a die-casting machine furnace insulation furnace. In some implementation manners of the present application, the carburized zinc alloy billet is placed in a vacuum sintering furnace with a negative pressure of 10MPa-15MPa, and the temperature is increased to the sintering temperature at a heating rate of 5℃ / min-10℃ / min, and the sintering temperature is the terminal temperature of the heating. The sintering temperature is 450℃-750℃, and the sintering time is 2h-4h. In some embodiments of the present application, the heating rate may be, for example, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min; the sintering temperature may be, for example, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C; the sintering time may be, for example, 2h, 2.5h, 3h, 3.5h, 4h. In some specific embodiments of the present application, the heating rate is 5°C / min-8°C / min, the sintering temperature is 550°C-650°C, and the sintering time is 2.5h-3.5h. The appropriate heating rate can avoid uneven heating inside and outside the carburizing alloy billet, which leads to inconsistent volume shrinkage or expansion, and thus irregular deformation of the final carburizing zinc alloy; sintering is carried out under negative pressure to avoid oxidation or other adverse chemical reactions of the components in the carburizing zinc alloy; each component is in a molten state at this sintering temperature and sintering time, and in the molten state, the components flow, diffuse, melt, crystallize, etc., which can eliminate part or all of the pores, avoid local component adhesion, and achieve full alloying and densification.
[0044] In the embodiment of the present application, the cooling method is natural cooling with the furnace, which can avoid the infiltration of gas during the forming process of the carburizing zinc alloy and the formation of holes on its surface or inside. On the one hand, it will reduce the mechanical properties of the carburizing zinc alloy, and on the other hand, it will cause depressions or protrusions on the surface of the carburizing zinc alloy. When it is subsequently used as the negative electrode of the battery, it is very easy to generate zinc dendrites in the uneven surface area.
[0045] In the embodiment of the present application, the rolling method includes hot rolling, and the hot rolling temperature is 250° C.-350° C., for example, but not limited to 250° C., 280° C., 300° C., 320° C., 350° C. Re-rolling the carburized zinc alloy is beneficial to reducing the volume of the negative electrode sheet, and further improving the material density, mechanical strength and energy density of the carburized zinc alloy negative electrode sheet.
[0046] In the embodiment of the present application, the thickness of the finally prepared carburized zinc alloy negative electrode sheet is 0.1 mm-0.5 mm, for example, but not limited to 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm; its compaction density is 6.1 g / cm 3 -7g / cm3 , for example but not limited to 6.1 g / cm 3 、6.2g / cm 3 、6.3g / cm 3 、6.4g / cm 3 、6.5g / cm 3 、6.6g / cm 3 、6.7g / cm 3 、6.8g / cm 3 、6.9g / cm 3 , 7g / cm 3 The carburized zinc alloy negative electrode sheet has a suitable thickness to avoid deformation or adverse effects on mass transfer during battery charging and discharging. The appropriate compaction density helps to shorten the distance between particles and thus reduce the internal resistance of the carburized zinc alloy negative electrode sheet, while avoiding excessive rolling to reduce or even block the ion channel, thereby hindering the rapid movement of ions and reducing the discharge capacity of the battery;
[0047] The preparation method provided in the present application uses powder metallurgy to make zinc powder, primary corrosion-resistant metal powder and conductive carbon material into a carburized zinc alloy negative electrode sheet, and controls the powder particle size and compaction density of the raw materials to give it suitable mechanical strength and machinability. The uniform distribution and full alloying of each component give the material a continuous and uniform conductive network from the inside to the outside, so that it has the advantages of high zinc utilization, strong conductivity and corrosion resistance as a battery negative electrode, and can significantly extend the cycle life of the battery. The preparation method is efficient, low-cost, has no cutting loss, is environmentally friendly, and is suitable for large-scale production of carburized zinc alloys.
[0048] The present application provides a carburized zinc alloy negative electrode sheet, which is prepared by the preparation method provided in the present application. The primary corrosion-resistant metal in the material can improve its corrosion resistance and mechanical strength; the carbon material is evenly distributed in the alloy to form a continuous three-dimensional conductive network, which reduces the internal resistance of the electrode. At the same time, the hydrophobicity of the carbon material also helps the desolvation of zinc ions during charging and converts them into zinc deposited on the negative electrode, inhibiting water molecules from entering the interior of the electrode and causing corrosion side reactions. The carburized zinc alloy negative electrode sheet is prepared by alloying zinc powder, primary corrosion-resistant metal powder and conductive carbon material. On the one hand, compared with the coating method of coating zinc powder on a metal foil current collector as a battery negative electrode, the embodiment of the present application does not need to set a metal foil current collector, and can also ensure that the battery has high energy density and electrode stability, which can save costs to a certain extent; on the other hand, compared with the use of carbon material to wrap zinc alloy as a battery negative electrode, the carburized zinc alloy negative electrode sheet provided by the present application is integrally formed, and the conductive components are evenly and continuously distributed throughout the zinc electrode, which helps to reduce the internal resistance of the electrode, accelerate ion conversion and electron flow, and does not cause problems such as powder loss, surface detachment, and material rebound, which can significantly improve battery performance and extend the battery cycle life.
[0049] In the embodiment of the present application, the conductivity of the carburized zinc alloy negative electrode sheet is 0.8×10 4 S / m-1.2×10 4 S / m, compacted density is 6.1g / cm 3 -7g / cm 3 , thickness is 0.1mm-0.5mm.
[0050] The present application also provides a zinc ion battery, which uses the carburized zinc alloy negative electrode sheet provided above in the present application as an electrode. The material can enhance the electrode conductivity and the desolvation of zinc ions, help zinc ions to achieve reversible and rapid embedding and extraction in the electrode, achieve reversible and rapid deposition and dissolution in an aqueous electrolyte, and slow down the corrosion of water molecules on the zinc electrode and other corrosion side reactions.
[0051] In the embodiment of the present application, the zinc ion battery includes an aqueous zinc ion battery, which has high energy density and excellent cycle performance compared to conventional aqueous batteries, extends the service life of the battery, is environmentally friendly, and has good application prospects in replacing lithium ion batteries in the future.
[0052] In some embodiments of the present application, an aqueous zinc ion battery comprises a positive electrode, a negative electrode, a diaphragm and an aqueous electrolyte disposed between the positive electrode and the negative electrode, wherein the negative electrode comprises the carburized zinc alloy negative electrode sheet provided above in the present application; the positive electrode may be, for example, but not limited to, one of an oxide material, a carbon material, a zinc material, a vanadium-based material, and a composite material of an oxide and a carbon material; the diaphragm may be, for example, but not limited to, one of a polyvinylidene fluoride (PVDF) film, a polypropylene (PP) film, and a polyvinyl alcohol (PVA) film; the aqueous electrolyte comprises an aqueous zinc salt solution, for example, but not limited to, one of a zinc sulfate solution, a zinc nitrate solution, a zinc chloride solution, a zinc acetate solution, and a zinc perchlorate solution, and the concentration thereof is 1 mol / L-3 mol / L, for example, but not limited to, 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, and 3 mol / L. In some specific embodiments of the present application, the aqueous electrolyte is a zinc sulfate solution, and the concentration thereof is 1.8 mol / L-2.2 mol / L.
[0053] The zinc ion battery provided in this application can be applied to wearable electronic devices, portable electronic products, energy storage, emergency power supply and other fields.
[0054] The technical solution of the present application is further described below with multiple embodiments.
[0055] Example 1
[0056] (1) Weigh zinc powder and chromium powder with a D50 particle size of 0.1 μm and a specific surface area of 62 m2 in a mass ratio of 94:2:4.2 / g of acetylene black, the purity of the three materials is all 99.99%, and they are placed in a vacuum induction furnace and mixed at a speed of 70r / min for 90min until the components are uniform to obtain a mixture.
[0057] (2) placing the mixed material in a tablet press for pressing to obtain a carburized zinc alloy compact; then placing the carburized zinc alloy compact in a vacuum sintering furnace, evacuating to a negative pressure of 15 MPa, heating to 600° C. at a heating rate of 5° C. / min, and sintering for 3 h, cooling naturally to room temperature in the furnace, and then taking out to obtain a carburized zinc alloy;
[0058] (3) The carburized zinc alloy was sliced and hot-rolled at 300° C. to obtain a carburized zinc alloy negative electrode sheet of 5 cm long × 5 cm wide × 0.5 mm thick.
[0059] Example 2
[0060] The only difference from Example 1 is that the primary corrosion-resistant metal powder added is nickel powder.
[0061] Example 3
[0062] The only difference from Example 1 is that the added conductive carbon material is carbon fiber.
[0063] Comparative Example 1
[0064] The only difference from Example 1 is that the mass ratio of zinc powder: chromium powder: acetylene black is 92:2:6.
[0065] Comparative Example 2
[0066] The only difference from Example 1 is that the mass ratio of zinc powder: chromium powder: acetylene black is 97.5:2:0.5.
[0067] Comparative Example 3
[0068] The only difference from Example 1 is that acetylene black is not added and the mass ratio of zinc powder to chromium powder is 98:2.
[0069] Comparative Example 4
[0070] The only difference from Example 1 is that no chromium powder is added and the mass ratio of zinc powder to acetylene black is 98:2.
[0071] Comparative Example 5
[0072] The only difference from Example 1 is that no chromium powder and acetylene black are added.
[0073] The conductivity and compaction density of the carburized zinc alloy negative electrode sheets prepared in the above Examples 1-3 and Comparative Examples 1-5 were tested; and each was assembled into a zinc-zinc symmetrical battery, the electrolyte was a 2 mol / L zinc sulfate solution, and the current density was set to 10 mA cm-2 , with a capacity of 5 mAh cm -2 , and perform continuous cycle charging and discharging with a period of 30 minutes until the battery fails, and record the failure time of each battery to test the cycle performance of the zinc-zinc symmetrical battery.
[0074] The test results of the conductivity, compaction density and battery cycle performance of Examples 1-3 and Comparative Examples 1-5 are shown in Table 1:
[0075] Table 1 Symmetrical battery cycle performance test results
[0076] serial number Conductivity (S / m) <![CDATA[Compaction density (g / cm 3 )]]> Battery failure time (h) Example 1 <![CDATA[1.1×10 4 ]]> 6.5 540 Example 2 <![CDATA[0.95×10 4 ]]> 6.8 510 Example 3 <![CDATA[1×10 4 ]]> 6.5 525 Comparative Example 1 <![CDATA[1.4×10 4 ]]> 6.2 310 Comparative Example 2 <![CDATA[0.8×10 4 ]]> 6.7 220 Comparative Example 3 <![CDATA[0.7×10 4 ]]> 7 170 Comparative Example 4 <![CDATA[0.6×10 4 ]]> 6.3 190 Comparative Example 5 <![CDATA[0.4×10 4 ]]> 6.5 42
[0077] The embodiments of the present application generally regard batteries with a battery failure time of less than 350 hours as unusable batteries. It can be seen from the test results in Table 1 that the battery failure time of Examples 1-3 exceeds 350 hours, and the batteries of Comparative Examples 1-5 fail before 350 hours under continuous charge and discharge, and can all be regarded as unusable batteries.
[0078] In Examples 1-3, carburized zinc alloy is prepared by simultaneously introducing an appropriate amount of primary corrosion-resistant metal powder (chromium powder or nickel powder) and a conductive carbon material into zinc powder. When this material is used as the negative electrode of the battery, the failure time of the battery under continuous cycle charge and discharge is more than 500 hours, which is 1.7 to 10 times longer than that of the battery in Comparative Examples 1-5.
[0079] The only difference between Example 2 and Example 1 is the added primary corrosion-resistant metal powder. The battery failure rate of the latter is slower because chromium has slightly stronger corrosion resistance than nickel. The only difference between Example 3 and Example 1 is the added conductive carbon material. The battery failure rate of the latter is slower because the specific surface area of acetylene black is slightly larger than that of carbon fiber, which improves the hydrophobicity of the electrode and can inhibit the occurrence of water-induced side reactions to a certain extent, thereby extending the cycle life of the battery.
[0080] The difference between Comparative Examples 1-3 and Example 1 is only that the amount of acetylene black added is different:
[0081] ① In Comparative Example 1, the amount of acetylene black added exceeds 5%. The battery failure rate of Comparative Example 1 is significantly accelerated compared with that of Example 1. This is because excessive addition of acetylene black causes carbon aggregation, forming an uneven three-dimensional conductive network in the carburized zinc alloy, which in turn leads to inconsistent electron circulation speed inside the zinc electrode, thereby affecting the stability and cycle life of the battery during multiple continuous cycles of charge and discharge.
[0082] ② In Comparative Example 2, the amount of acetylene black added is less than 2%, and no acetylene black is added in Comparative Example 3. The battery failure time of Comparative Example 2-3 is shortened by half or more relative to that of Example 1 because the amount of acetylene black added is too small or no acetylene black is added, which is insufficient to achieve its beneficial effects of conductivity, hydrophobicity and corrosion resistance; however, compared with Comparative Example 3, the battery cycle performance of Comparative Example 2 is better, reflecting the effect of adding an appropriate amount of acetylene black on extending the battery life.
[0083] Based on the test results of Example 1 and Comparative Examples 1-3, it is demonstrated that the solution provided in the present application of introducing 2%-5% by mass of conductive carbon material into zinc alloy is important for slowing down the battery failure rate and extending the battery cycle life.
[0084] The only difference between Comparative Example 4 and Example 1 is that no primary corrosion-resistant metal powder is added, but the battery failure time of the two differs by more than two times. This is because Example 1 has stronger corrosion resistance, which inhibits or slows down the corrosion of the electrodes caused by water molecules or other components in the electrolyte, thereby extending the cycle life of the battery.
[0085] The electrode material of Comparative Example 5 is only metallic zinc, and no alloy is formed. Its mechanical properties, physical properties and chemical properties are far inferior to those of zinc alloy electrodes. During the battery charging and discharging process, the oxide film on the surface of the pure zinc electrode is quickly corroded and removed, and the pure zinc electrode is passivated. The battery fails after 42 cycles of charge and discharge.
[0086] In summary, the preparation method provided in the present application adopts powder metallurgy to make zinc powder, an appropriate amount of primary corrosion-resistant metal powder and a conductive carbon material into a carburized zinc alloy negative electrode sheet, which is used as an electrode of a zinc ion battery. It has excellent conductivity and corrosion resistance, can effectively improve the battery energy density and cycle stability, and significantly extend the number of cycles and service life of the battery.
[0087] The above disclosure is only the preferred embodiment of the present application, and cannot be used to limit the scope of rights of the present invention. Ordinary technicians in this field can understand that all or part of the processes of implementing the above embodiments and making equivalent changes according to the claims of the present invention still fall within the scope covered by the present invention.
Claims
1. A method for preparing a carburized zinc alloy negative electrode sheet, characterized in that: include: Mixing zinc powder, primary corrosion-resistant metal powder and conductive carbon material to form a mixture, and preparing a carburized zinc alloy negative electrode sheet by powder metallurgy. The mass percentage of the conductive carbon material in the mixture is 2%-5%.
2. The method for preparing a carburized zinc alloy negative electrode sheet according to claim 1, characterized in that: The conductive carbon material includes one or more of acetylene black, carbon fiber, graphene, carbon nanotube, conductive carbon black, conductive graphite, and Ketjen black.
3. The method for preparing a carburized zinc alloy negative electrode sheet according to claim 1 or 2, characterized in that: The specific surface area of the conductive carbon material is 60 m 2 / g-70m 2 / g.
4. The method for preparing a carburized zinc alloy negative electrode sheet according to claim 1, characterized in that: The primary corrosion-resistant metal powder includes one or more of chromium powder, nickel powder, molybdenum powder, titanium powder, zirconium powder, tantalum powder, tin powder and niobium powder.
5. The method for preparing a carburized zinc alloy negative electrode sheet according to claim 1, characterized in that: The D50 particle size of the zinc powder and the primary corrosion-resistant metal powder is 0.1 μm-0.5 μm; and / or, The mass percentage of the primary corrosion-resistant metal powder in the mixed material is 2%-4%.
6. The method for preparing a carburized zinc alloy negative electrode sheet according to claim 1, characterized in that: The process of preparing the carburized zinc alloy negative electrode sheet by powder metallurgy is specifically as follows: The mixed material is sequentially subjected to sheeting, sintering, cooling, slicing and rolling to obtain a carburized zinc alloy negative electrode sheet.
7. The method for preparing a carburized zinc alloy negative electrode sheet according to claim 6, characterized in that: The sintering is performed under a negative pressure of 10MPa-15MPa, the sintering temperature is 450°C-750°C, and the sintering time is 2h-4h.
8. The method for preparing a carburized zinc alloy negative electrode sheet according to claim 1, characterized in that: The conductivity of the carburized zinc alloy negative electrode sheet is 0.8×10 4 S / m-1.2×10 4 S / m; and / or, The compaction density of the carburized zinc alloy negative electrode sheet is 6.1 g / cm 3 -7g / cm 3 .
9. A carburized zinc alloy negative electrode sheet prepared by the preparation method according to any one of claims 1 to 8.
10. A zinc ion battery, characterized in that: It comprises a carburized zinc alloy negative electrode sheet prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Nonaqueous electrolyte secondary battery
CN102447129A
Preparation method of zinc antimony alloy-carbon composite negative electrode material
CN103219495A
Composite zinc cathode with multiphase material
CN110364692A
Zinc ion battery negative electrode material, zinc ion battery negative electrode and zinc ion battery
CN118016867A
Sodium-aluminum-lithium-carbon multi-component alloy as well as preparation method and application thereof
CN118497578A